Somatic SDHA mutations in paragangliomas in siblings: Case report of 2 cases. Issue 41 (9th October 2020) - Huang, Yen-Chun; Chang, Hsiao-Huang; Chen, Ming-Huang; Huang, Kuo-Hung; Li, Anna Fen-Yau; Lin, Chien-Hsing; Shyr, Yi-Ming; Fang, Wen-Liang
Abstract: Rationale: Paragangliomas (PGLs) are rare neuroendocrine tumors that are strongly influenced by genetics, and succinate dehydrogenase-deficient PGLs appear to constitute one of the most important categories. Interestingly, somatic PGLs only possess genomic alterations involving the SDHB and SDHD subunits, and no SDHA alterations have been described. Here, we are presenting the clinical and genetic analyses of 2 cases with the first somatic SDHA variant identified in PGLs. Patient concerns: Here, we reported 2 family members with the diagnosis of PGL. Patient 1 is a 55-year-old woman with a functionally perigastric PGL that co-occurred with a gastric gastrointestinal stromal tumor (GIST), and patient 2 is a 43-year-old woman with a nonfunctionally pericardial PGL, who was the younger sister of the first patient. Diagnoses: Imaging surveys of the 2 cases depicted the presence of a perigastric and a pericardial mass, respectively. A diagnosis of paragangliomas was established by immunohistochemistry (IHC). Interventions: Both patients underwent single-stage resection of the lesion after preoperative oral α-adrenoceptor therapy for 2 weeks. We later performed comprehensive genomic profiling on the tumor samples, including PGL and GIST from patient 1 and PGL from patient 2, and searched for novel actionable mutations, including in all succinate dehydrogenase subunits, as the IHC results were negative for SDHB . Outcomes: Both patients had an uneventful recovery after surgery and the sequencing showed a novel somatic variant in the SDHA gene on chromosome 5q11 (c.1945_1946delTT). Regular follow-up with biochemical testing and image studies showed no evidence of recurrence after a year for patient 1 and 6 years for patient 2. Lessons: PGLs often lead to considerable diagnostic difficulty due to their multiple anatomical locations and variable symptoms, as presented by our cases. The comprehensive use of images and plasma/urine catecholamine measurement can aid the diagnosis of PGLs. In addition, our findings also demonstrate the usefulness and importance of genetic analysis of SDHA mutations in patients exhibiting SDHB IHC-negative PGL. Additional studies utilizing comprehensive genomic profiling are needed to identify the group of PGLs harboring this SDHA genomic alteration. Abstract : Supplemental Digital Content is available in the text